African democracy and development challenges for post-conflict African nations - Cassandra R. Veney & Dick Simpson (Lanham Lexington Books, 2013)
The book includes an examination of the various actors who are involved in post-conflict rebuilding and reconstruction that involves internal and external participants. For example, it is clear that the internal actors involve Africans themselves as ordinary citizens, members of local and national governments, and members of non-governmental organizations. This allows the reader to understand the agency and empowerment of Africans in post-conflict reconstruction. Various institutions are addressed within the context of the roles they play in establishing governance organizations such as the Truth and Reconciliation Commission in Sierra Leone, the African Union, chiefs in Liberia, and non-governmental organizations. Furthermore, the external actors who are involved in post-conflict reconstruction are examined such as international non-governmental organizations and the African Diaspora. They both have their own constituents and agendas and can and do play a positive and negative role in post-conflict reconstruction. It is obvious that countries that are addressed in the book are in dire need of financial assistant to rebuild much needed infrastructure that was destroyed during the conflict. All of the countries covered in the book need schools, medical facilities, roads, bridges, airports, ports, and the government does not have the money to provide these. This is where the international non-governmental organizations and the African Diaspora play an important role. The chapters that address these issues are cognizant of their importance and at the same time, the authors realize that sovereignty can be undermined if Africans are not in the forefront of policy and decision making that will determine their future.
Includes bibliographical references and index.
Keywords: Postwar reconstruction -Africa, Sub-Saharan -Congresses.